Repercussions of microplastics and nanoplastics on the gastrointestinal, circulatory and respiratory systems: A new potential for exposure (Research, Society and Development, 2024)
Objective: Understand the forms of contamination and the consequences of microplastics and nanoplastics for the gastrointestinal, respiratory and cardiovascular systems. Methods: Integrative review using the Pubmed, SciELO, LILACS and Cochrane database platforms. The research was carried out using the search strategy: (“human health”) AND (“cell interaction”) OR (“microplastics”). A total of 489 articles were found. After applying the inclusion and exclusion criteria, 25 articles were selected, with 20 articles being removed after the initial analysis. This totaled 5 articles for full analysis. Results: Extensive damage from plastic particles to human health is evident. In the gastrointestinal system, increased local inflammation causes barrier dysfunction and reduced digestion of certain macromolecules. In the respiratory system, the reduction in mucociliary clearance leads to an increase in pathogens and a retention of debris, coming from external air, in the lung. In the cardiovascular system, changes in heart rate, as well as an increased risk of thrombosis are findings due to the presence of MPs and NPs. Conclusion: An integrated view of the damage caused by MPs and NPs and their interactions with human cells is concluded, but there is still no great evidence that allows us to assess the full extent of the damage.